Analysis of the effects of shading screens on the microclimate of greenhouses and glass facade buildings. (1st March 2022) - Santolini, Enrica; Pulvirenti, Beatrice; Guidorzi, Paolo; Bovo, Marco; Torreggiani, Daniele; Tassinari, Patrizia
Abstract: Shading devices are widely used in the Mediterranean area, since they reduce strong solar radiation effects in the closed environment. On the contrary, they have negative effects on the internal ventilation, especially if they have low porous texture limiting the air exchange with the external environment. This work aims to characterize by means of computational fluid dynamics the microclimate given by the use of shading devices in buildings with glass envelopes, such as greenhouses. The method is applied to a naturally ventilated glass greenhouse. Three commercial shading screens are compared, having typical porosity for the use in Mediterranean climate. The screens are modeled by means of porous materials, with the properties evaluated by experimental measurements of permeability. The numerical simulations are verified by a comparison with measurements of temperature and velocity within the greenhouse. In particular, the experimental setup is based on a novel and patented methodology which gives the exact position of the sensors within the greenhouse thanks to an acoustic referencing system. It is shown that screens with low permeability give optimal temperature distribution above the crops for the wind and air temperature conditions analyzed. The best screen position and permeability, for the environmental most frequent conditions in terms of solar radiation and wind directions with respect to orientation and position of the windows, were established. The methodology and the results shown in the work can be applied to different glass envelope buildings, to yield the best choice of shading screens in correspondence of given environmental characteristics. Highlights: The use of shading screens have complex effects on greenhouse environment. Temperature and air flow distributions are strongly different in cultivation area. A novel method for defining sensors positions is proposed and applied. A novel model coupling solar radiation and porous materials is considered.